Engaging children and adolescents in the design and conduct of paediatric research - Bierer, Barbara E.; Koppelman, Elisa; Croker, Alysha K.; Hosseinzadeh, Sharareh; Hovinga, Collin; Joffe, Steven; McMillan, Gianna; Nelson, Robert; Bucci-Rechtweg, Christina (Frontiers in Pediatrics, 2024)
The importance of patient engagement in product development and clinical research is widely acknowledged in clinical research. In pediatrics, parents and guardians are often vocal advocates for their children in the process, but investigators and sponsors rarely directly solicit children's or adolescents' perspectives in clinical research planning or as patient partners during the conduct of research. Here, we provide compelling reasons and recommendations for investigators and sponsors to systematically engage young people in the design, conduct, and review of research, and the premise that input will be incorporated as a routine expectation. We consider the theoretical, ethical, and practical implications of this approach.